Pengaruh Kepemilikan Institusional dan Kepemilikan Manajerial Terhadap Manajemen Laba - Fransiska Wahyu Lestari (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2022)
Earnings management is a management action in the process of preparing financial statements so as to increase or decrease accounting profits according to interests. Earning management that occurs in manufacturing companies is due to a conflict of interest between owner and manager. This study aims to determine the effect of Institutional Ownership and Managerial Ownership to Earning Management. The population of this study is a manufacturing company listed on the Indonesia Stock Exchange period 2014 - 2016. Selection of sample through purposive sampling method chosen with predefined criteria. The type of data used in this study is secondary data. The analytical method used is descriptive statistical analysis method, classical assumption test and hypothesis test using SPSS version 23 as the analytical tool. There are 24 companies that meet the criteria as a sample of research with observation data amounted to 72 data / cases with data disposal / case of 41 so that the observed data studied into 31 data/cases. The results of this study indicate that partially institutional ownership have no effect on earning management and managerial ownership effect on earning management. With increased managerial ownership, earning management will decrease. Can be concluded simultaneously based on the F test, independent variables consisting of institutional ownership and managerial ownership have an effect on earning management.